Social mix and housing policy: Local effects of a misleading rhetoric. The case of Milan. (January 2016) - Bricocoli, Massimo; Cucca, Roberta
The article focuses on different uses of the concept of social mix and on emerging criticalities of its use as a planning principle by discussing the results of empirical research on recent housing projects in Milan, Italy. Although the concept of social mix is generally represented as a tool to improve the living conditions of disadvantaged social groups, the praise for social mix in new housing projects may also be driven by the will of targeting the needs of specific medium–low income groups considered functional to urban growth, and by the increase of real estate values that it may provide. In urban contexts affected by a severe shortage of rental housing, social mix strategies may foster the exclusion of lowest-income groups from access to social housing and favour their segregation. Especially with reference to southern European cities, social mix risks becoming a catchword with paradoxical effects in local policy agendas and the topic of mixed communities becoming employed as a socio-political lever for developer-led, profit-making developments.